Transformations of the Monstrous Feminine in the New Asian Female Ghost Films. (February 2015) - Lee, Hunju
Since the financial success of the American remake of a Japanese horror film called Ringu (Hideo Nakata 1998), remaking a well-accepted Asian scary film in its domestic or pan-Asian market has been a recurring phenomenon in the American film industry for the past decade. The particular style of horror films which this article identifies as the "New Asian Female Ghost Films" has been the most welcomed Asian genre for the Hollywood project for reworking Asian cinematic originals. Beyond the commonality in narrative and thematic sharing, the New Asian Female Ghost Films are characterized as the specific iconography of the monstrous feminine with other gendered/gendering imageries and imaginations to reflect as well as the countries' long traditions of female ghost filmmaking and the changed socio-cultural matrixes.